An Investigation of Effects and Safety of Pipelines due to Twin Tunneling. (28th May 2021) - Yu, Shao; Lan, Riyan; Luo, Junhui; Duan, Zhibo; Ma, Shaokun
Abstract : To efficiently and accurately predict the effects of twin tunneling on adjacent buried pipelines, the effects of upward and downward relative pipeline-soil interactions were considered. A series of numerical parametric studies encompassing 8640 conditions were performed to investigate the responses of a pipeline to twin tunneling. Based on the dimensionless analysis and normalized calculation results, the concept of equivalent relative pipeline-soil stiffness was proposed. Additionally, expressions for the relative pipeline-soil stiffness and relative pipeline curvature and for the relative pipeline-soil stiffness and relative pipeline settlement were established, along with the related calculation plots. Relying on a comparison of prediction results, centrifuge model test results, and field measured results, the accuracy and reliability of the obtained expressions for predicting the bending strain and settlement of adjacent buried pipelines caused by twin tunneling were validated. Based on the calculation method, the maximum bending strain and maximum settlement of pipelines can be calculated precisely when the pipeline parameters, burial depth, soil parameters, and curve parameters of ground settlement due to tunneling are provided. The proposed expressions can be used not only to predict the maximum bending strain and maximum settlement of pipelines caused by single and twin tunneling but also to evaluate the effects of single and twin tunneling on the safety of existing buried pipelines. The relevant conclusions of this article can also provide a theoretical basis for the normal service of buried pipelines adjacent to subway tunnels.